2017
DOI: 10.1007/s10393-017-1240-2
|View full text |Cite
|
Sign up to set email alerts
|

Batrachochytrium dendrobatidis and the Decline and Survival of the Relict Leopard Frog

Abstract: Epizootic disease caused by the fungal pathogen Batrachochytrium dendrobatidis (Bd) is a major driver of amphibian declines, yet many amphibians declined before the pathogen was described. The Relict Leopard Frog, Rana onca (=Lithobates onca), was nearly extinct, with the exception of populations within a few geothermal springs. Growth of Bd, however, is limited by high water temperature, and geothermal springs may have provided refuge during outbreaks of chytridiomycosis. We conducted field surveys and labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Since virulence of Bd is thought to decrease with increased passages (transfers) in culture media (Langhammer et al, 2013), serial passages could be used to develop attenuated Bd vaccines; although, Bd virulence may depend on subculturing methods (Voyles et al, 2014). Indeed, the low-virulence of SLL in R. onca observed in a previous study (Jaeger et al, 2017) and in this current study could be due to the high passage number.…”
Section: Implementing Vaccines/exposure-clearance For Amphibian Conservationmentioning
confidence: 65%
See 2 more Smart Citations
“…Since virulence of Bd is thought to decrease with increased passages (transfers) in culture media (Langhammer et al, 2013), serial passages could be used to develop attenuated Bd vaccines; although, Bd virulence may depend on subculturing methods (Voyles et al, 2014). Indeed, the low-virulence of SLL in R. onca observed in a previous study (Jaeger et al, 2017) and in this current study could be due to the high passage number.…”
Section: Implementing Vaccines/exposure-clearance For Amphibian Conservationmentioning
confidence: 65%
“…We had previously confirmed the absence of Bd in this population using quantitative real-time PCR (qPCR) of swabs collected from 60 adult frogs using methods described below. We housed and maintained R. onca and R. pipiens in individual containers at 19°C following protocols previously described (Jaeger et al, 2017). We focused our efforts on frogs rather than tadpoles because the immune systems of amphibians at these distinct life stages are drastically different (Rhoo et al, 2019), and chytridiomycosis resistance or tolerance at the tadpole stage may not translate to adult stages (Waddle et al, 2019).…”
Section: Access To Animals and Captive Husbandrymentioning
confidence: 99%
See 1 more Smart Citation
“…Under certain circumstances, such as in particular species or with repeated priming, it may be possible for this adaptive immune response to function protectively and reduce mortality [163]. Circumstantial evidence concerning experimental animals suggests that adaptive immune memory may be involved in animals that recover from chytridiomycosis after 4-6 weeks post exposure or in animals that persist with low-level burdens indefinitely (as reported by [133,158,[164][165][166]). However, examples of improved survival associated with repeated immune priming may alternatively be due to increased reactivity of the innate response, known as an innate immune memory [167].…”
Section: The Clinical Adaptive Immune Response Is Generally Poor and mentioning
confidence: 99%
“…(2015) found that Bd can persist in Amargosa toads ( Anaxyrus nelsoni ) even during the spring and summer, when temperatures can exceed 30°C. Additionally, imperiled Mojave Desert species such as the relict leopard frog ( Rana onca ) can contract and succumb to Bd infection (Jaeger et al., 2017; Waddle et al., 2019).…”
Section: Introductionmentioning
confidence: 99%